Intercropping in sugarcane to boost farmer’s income - Upadhsaya, Bharati; Tiwari, R K; Kumar, Shailesh; Kumar, Sanjay (Indian Farming, 2020)
Sugarcane (Saccharum spp. hybrid complex), is a very important sugar crop belonging to the grass family Gramineae. On worldwide basis, sugarcane is cultivated in more than 100 countries, producing 178 million tonnes of sugar, nearly 80% of which is contributed by cane sugar. In India, it occupies about 2.53% (4.9 million ha) of the gross cropped area of the country with an annual production of 303.6 million tonnes. India is the second largest producer after Brazil producing nearly 15 and 25% of global sugar and sugarcane, respectively. Growing two or more crops simultaneously on the same field is known as intercropping. Crop intensification is in both temporal and spatial dimensions. Until recent years, sugarcane crop was cultivated as a single crop. But with increase in population, insufficient food, limited scope for expansion of cultivated area, diversified needs of small farmers for food and cash etc. have forced the adoption of intercropping systems.